Silk Sericin Semi-interpenetrating Network Hydrogels Based on PEG-Diacrylate for Wound Healing Treatment - Patchara Punyamoonwongsa; Supattra Klayya; Warayuth Sajomsang; Chanikarn Kunyanee; Sasitorn Aueviriyavit (International Journal of Polymer Science)
Silk sericin (SS) from the Bombyx mori silk cocoons has received much attention from biomedical scientists due to its outstanding properties, such as antioxidant, antibacterial, UV-resistant, and ability to release moisturizing factors. Unmodified SS does not self-assemble strongly enough to be used as a hydrogel wound dressing. Therefore, there is a need for suitable stabilization techniques to interlink the SS peptide chains or strengthen their structural cohesion. Here, we reported a method to form a silk semi-interpenetrating network (semi-IPN) structure through reacting with the short-chain poly(ethylene glycol) diacrylate (PEGDA) in the presence of a redox pair. Various hydrogels were prepared in aqueous media at the final SS/PEGDA weight percentages of 8/92, 15/85, and 20/80. Results indicated that all semi-IPN samples underwent a sol-gel transition within 70 min. The equilibrium water content (EWC) for all samples was found to be in the range of 70-80%, depending on the PEGDA content. Both the gelation time and the sol fraction decreased with the increased PEGDA content. This was due to the tightened network structure formed within the hydrogel matrices. Among all hydrogel samples, the 15/85 (SS/PEGDA) hydrogel displayed the maximum compressive strength (0.66 MPa) and strain (7.15%), higher than those of pure PEGDA. This implied a well-balanced molecular interaction within the SS/PEGDA/water systems. Based on the direct and indirect MTS assay, the 15/85 hydrogel showed excellent in vitro biocompatibility towards human dermal fibroblasts, representing a promising material for biomedical wound dressing in the future. A formation of a semi-IPN structure has thus proved to be one of the best strategies to extend a practical limit of using SS hydrogels for wound healing treatment or other biomedical hydrogel matrices in the future.